(untitled) (Journal of Engineering, 2021)
The main objective of this study is to understand the work of the pile caps made of lightweight aerated foam concrete and study the many factors affecting the ability and the capacity of the shear. The study was done by analyzing previous practical and theoretical experiences on the reinforced concrete pile caps. The previous practical results indicated that all specimens failed by shear diagonal compression or tension modes except one specimen that failed flexural-shear mode. Based on test specimens’ practical results and behavior, some theoretical methods for estimating the ultimate strength of reinforced concrete pile caps have been recommended, some of which evolved into the design documents available on the subject. A theoretical and practical study of compression concluded that the shear capacity is limited by the nodal zone bearing stresses. The flexural capacity can be described by the column load that would cause the yielding of the tie (i.e., steel reinforcement). Therefore, the design of pile caps should include a check on bearing strength to be added to the traditional section force approach for pile cap design.